The Potential for Developing Educational Tourism as a Source for Learning Biology in the Nantu–Boliyohuto Wildlife Sanctuary Buffer Zone - Ntolu, Deltias; Ibrahim, Mustamin; Hamidun, Marini Susanti; Baderan, Dewi Wahyuni K.; Husain, Ilyas H. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
This study analyzed the potential of educational tourism as a Biology learning resource in the buffer zone of the Nantu–Boliyohuto Wildlife Reserve, Gorontalo. A descriptive qualitative approach was employed. Data were collected through field observations, semi-structured interviews with 12 informants, documentation, and field notes at four observation stations representing different habitat types. Data were analyzed using qualitative descriptive techniques involving data reduction, data display, and conclusion drawing, while source triangulation ensured validity. The findings revealed high biotic potential, including diverse flora and fauna, and abiotic potential, such as air temperature, soil pH, light intensity, vegetation structure, and habitat variation. These characteristics are relevant to senior high school Biology topics, including biodiversity, ecosystems, classification, adaptation, conservation, and human–environment interactions. The area can support field-based learning through species identification, ecosystem observation, environmental measurements, and conservation projects. Strong community support and relatively natural environmental conditions enhance its educational tourism potential. However, limited road access, inadequate interpretation boards, lack of observation trails, and insufficient learning facilities remain challenges. Overall, the buffer zone has strong potential to be developed as a conservation-based educational tourism destination that supports Biology learning through active community involvement.